Outcomes of cardiovascular risk factors screening programme among employees of a Malaysian public university - Liau , Siow Yen; Mohamed Izham, Mohamed Ibrahim; Hassali, Mohamed Azmi; Shafie, Amir Akramin; Othman, Ahmad Tajuddin; Nik Mohamed, Mohamad Haniki; A Hamdi, Menal (JCDR Research and Publications (P) Limited, 2010)
Background: The burden on cardiovascular disease in Malaysia is in the increasing trend and this is associated with a number of risk factors. Aim: This study aims to explore the prevalence of major cardiovascular risk factors among employees of Engineering Campus, Universiti Sains Malaysia. Design: A cross-sectional study was carried out from 19th February 2009 to 12th March 2009. Methods and Materials: Data on eight established risk factors were collected. Statistical Analysis: Descriptive statistic was used to describe the prevalence of risk factors among the study subjects. Multiple logistic regression analysis was used to explore the clustering of risk factors (having two or more risk factors). All data were analyzed using statistical software SPSS package version-16 and a two-tailed p-value < 0.05 was considered to be statistically significant. Results: A total of 217 (27.7%) respondents participated in the screening exercise. Results from this screening showed that risk factors such as unhealthy diet (92.1%), overweight/obesity (73.3%) and physical inactivity (65.0%) were highly prevalent. The median number of risk factors was 3 (IQR=2). In addition, most of the subjects (n=203, 93.5%) were categorized as being in high risk for future cardiovascular events as according to the definition of National Cholesterol Education Program. Respondents with clustered risk factors were older, had lower intake of fruit and vegetables, less physically active, had a higher body mass index, systolic blood pressure, diastolic blood pressure and fasting blood glucose. Further analysis found that fruit and vegetable intake, physical activity and body mass index formed a good predictive model for prediction of clustered risk factor model with a Nagelkerke R-squared value of 0.529. Conclusion: There is a high prevalence of cardiovascular risk factors among USM employees and these risk factors tend to cluster. It is therefore recommended that prompt actions should be taken to overcome and modify these risk factors.